PROSPECTS OF MODERN LEGAL EDUCATION - Amirov Elbek (Scholars Digest Publishing, 2023)
The article covers issues such as increasing the competitiveness of national legal education, further expanding the opportunities of our youth in legal education, bringing the quality of legal education to the level that meets international standards, in general, quality legal education in line with the times, forming a team of lawyers in line with the times.
Keywords: Globalization, integration, processes, legal education, framework of the law increases.